Becoming Mary Sully : toward an American Indian abstract - Deloria, Philip Joseph (University of Washington Press, 2019)
Dakota Sioux artist Mary Sully was the great-granddaughter of respected nineteenth-century portraitist Tomas Sully, who captured the personalities of America's first generation of celebrities (including the figure of Andrew Jackson immortalized on the twenty-dollar bill). Born on the Standing Rock reservation in South Dakota in 1896, she was largely self-taught. Steeped in the visual traditions of beadwork, quilling, and hide painting, she also engaged with the experiments in time, space, symbolism, and representation characteristic of early twentieth-century modernist art. And like her great-grandfather Sully was fascinated by celebrity: over two decades, she produced hundreds of colorful and dynamic abstract triptychs, a series of "personality prints" of American public figures like Amelia Earhart, Babe Ruth, and Gertrude Stein. Sully's position on the margins of the art world meant that her work was exhibited only a handful of times during her life. In Becoming Mary Sully, Philip J. Deloria reclaims that work from obscurity, exploring her stunning portfolio through the lenses of modernism, industrial design, Dakota women's aesthetics, mental health, ethnography and anthropology, primitivism, and the American Indian politics of the 1930s. Working in a complex territory oscillating between representation, symbolism, and abstraction, Sully evoked multiple and simultaneous perspectives of time and space. With an intimate yet sweeping style, Deloria recovers in Sully's work a move toward an anti-colonial aesthetic that claimed a critical role for Indigenous women in American Indian futures -- within and distinct from American modernity and modernism.